TCH-051 Validation of an Automated Compounder Set Up Once a Week For Parenteral Nutrition Solutions. (12th March 2013) - Bouchoud, L; Sadeghipour, F; Fleury, S; Bonnabry, P
Abstract : Background: Our parenteral nutrition production (PN) decreased after we introduced standard solutions. To keep just a small number of daily PN items cost-effective, we decided to validate a once a week setting up of an automated compounder device (ACD). Purpose: To test the operation and performance of an ACD (Baxa MM12) for a once a day and a once a week use. Materials and Methods: Accuracy (mean in % of the expected value) and precision (Coefficient of Variation) of the ACD was evaluated by weighing different volumes of water 10 times (0.5 to 40 mL; daily operational qualification) and different volumes of nutrients (0.5 to 100 mL; daily performance qualification) over 3 consecutive days. The concentration of nutrients (glucose, Na and K) in PN, particulate contamination and media-fill tests were checked each day while the machine's settings were only adjusted once a week (3 consecutive weeks). Some bottles were changed during the week and other remained in place, according to a predefined protocol. The ACD was installed in a laminar airflow hood GMP Class A with a cleanroom Class B background and a temperature around 20°C. Results: Daily operational and performance results: The concentrations of nutrients in PN products made weekly always met the specifications (internal limits ±15% for Na, ±10% for glucose and −15% to +10% for K). No particles or microbiological contamination were detected. Conclusions: Validation proved the acceptable accuracy, precision and aseptic conditions in the course of the week. A sepsis can only be guaranteed by a strict application of GMP in a high quality compounding environment. In those conditions, PN products can be produced safely for one week with the same settings. Setting it just once a week saves technician time (300 hours/year) and money (15, 000 Euro/year). No conflict of interest.